2011
DOI: 10.4236/jbnb.2011.24052
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthesis Route to Produce Boron Nitride Nanotubes for Bioapplications

Abstract: Nanostructures of boron nitride have attracted a great deal of interest due to their potential applications that comprise a broad range of topics, including biomedical technology, since it presents good chemical stability and suggests good biological inertia. This paper reports a facile and effective synthesis based on CVD process with new conditions to produce boron nitride nanotubes in higher amount using boron powder, ammonium nitrate and hematite as catalysts in tubular furnace, without using extreme condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…This study demonstrated that even at the highest concentration, the cell viability was higher than 70%. This result reassures the findings of previous studies [29,37,38], confirming that, in concentrations below 200 μg/mL, BNNTs showed low cytotoxicity, and BNNTs do not appear to inhibit cell growth or induce apoptotic pathways in the cells. It should be noted that the high purity and quality of BNNTs are crucial for their nontoxicity [11,36].…”
Section: Boron Nitride Functionalization and Its Implications In Nanosupporting
confidence: 90%
See 1 more Smart Citation
“…This study demonstrated that even at the highest concentration, the cell viability was higher than 70%. This result reassures the findings of previous studies [29,37,38], confirming that, in concentrations below 200 μg/mL, BNNTs showed low cytotoxicity, and BNNTs do not appear to inhibit cell growth or induce apoptotic pathways in the cells. It should be noted that the high purity and quality of BNNTs are crucial for their nontoxicity [11,36].…”
Section: Boron Nitride Functionalization and Its Implications In Nanosupporting
confidence: 90%
“…The adequate modification process provides specific surfaces that allow its better solubility or dispersion in different solvents media playing an important role regarding selectivity, for instance, in biological systems [28]. These nanoparticles can be coated with biological molecules to facilitate their interaction with a living system, binding to a specific target, like tumor cells [29]. Regarding the tumor targeting strategies, the enhanced permeability and retention (EPR) effect of nanomaterials is a key mechanism for solid tumor targeting, and it is considered a gold standard for novel radioisotopes design [30].…”
Section: Boron Nitride Functionalization and Its Implications In Nanomentioning
confidence: 99%
“…This may be attributed to evaporation of water molecules. After 300 °C the line shows the thermal stability of boron nitride even at high temperature 62 .…”
Section: Resultsmentioning
confidence: 95%
“…The study found that the PEG 1000 -BNNT and CH-BNNT were cytotoxic at high concentrations (100 g/mL) while the GA-BNNT was not cytotoxic. Moreover, the hemocompatibility study of the unmodified BNNTs showed that they were hemocompatible on the malignant U87 (wild type p53) and T98 (mutant p53) glioblastoma, MCF-7 adenocarcinoma mammary gland cells and normal MRC-5 fibroblast lung cells [18].…”
Section: Introductionmentioning
confidence: 99%